HISTORY OF THE PRODUCTION AND USE OF ROMAN CEMENT IN ARCHITECTURE OF THE 19TH CENTURY - Fedoryshyn, Andriy; Rybchynskyi, Oleg (Theory and practice of design, 2025)
The discovery of Roman cement by Parker in 1796 was preceded by a long journey from Roman concrete to Smithon’s “water lime”. Initially, it was produced from septaria, later from marls and dolomites. In the first half of the 19th century, along with England, cement was actively produced in France and Germany, and later production spread to the rest of Europe and America. Depending on the region, it is called Roman cement, fast natural cement, or names belonging to the area. It plays a key role in the development of the transport infrastructure of countries. Thanks to the innovations of the French and Italians, it becomes an integral part of the decoration of buildings. It plays an important role in the formation of reinforced concrete, but later it is inferior to Portland cement. The period of use of Roman cement is characterized by the transition from traditional architecture from natural stone to artificial stone, and its further transformation into reinforced concrete. Purpose: to investigate the features of the production and use of Roman cement in the architecture of the 19th century. Methodology. Method of systematization and synthesis of literary sources, content analysis, data interpretation, generalization of results Results. The importance of pozzolana and trass, as hydraulic additives that played a key role in hydraulic engineering until the end of the 18th century, is determined. The features of the production and use of hydraulic lime are established. The factors that influenced the emergence of Roman cement in England, its development and the subsequent search for alternative binders, which led to the emergence of Portland cement, are highlighted. The prerequisites that influenced the rapid development of the use of Roman cement in France as a structural and decorative material and its spread throughout Europe are considered. The role of Italy in the beginning of the use of Roman cement as a decorative and finishing material is determined. The development of technologies in France that influenced the transition from artificial stone to reinforced concrete structures is considered. Scientific novelty. The role and place of Roman cement in the development and formation of 19th century architecture is determined. Practical relevance. A holistic understanding of the spread of the use of Roman cement in 19th century architecture is formed. Data on the beginning of the use and production of Romanesque cements in different countries are systematized. The key features of the development of both cement production technologies and their application in the 19th century are considered.